FLOOD SUSCEPTIBILITY MAPPING: A REVIEW TO PREPARE RISK MITIGATION FRAMEWORK (International Journal of Food and Nutritional Sciences, 2022)
Flooding become an environmental threat that challenges vulnerability of ecosystem and communities in the immediate vicinity. Such disasters are expected to increase with the climate change scenarios, growing population pressure and urbanization. To curb the damage caused by flood, it is important to understand role of conditioning factors towards flood occurrence and implementation of management strategies. Flood susceptibility mapping provides a better solution towards curbing the losses.Though the distribution of flood susceptibility will be highly dependent on the terrain conditions, the flood plains is determined by the drainage pattern and run off. Flood susceptibility modelling would enhance the adaptation frame works for the less studied disasters and their dynamics in the climate change scenarios and urbanizatio